2022
DOI: 10.1007/s00268-022-06537-6
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Parathyroidectomy: Can Intraoperative Parathyroid Hormone Monitoring be Omitted?

Abstract: Background Intraoperative PTH (ioPTH) monitoring has become widely accepted in the era of minimally invasive parathyroidectomy (MIP). The purpose of this study was to evaluate the need for ioPTH during parathyroidectomy in patients with positive preoperative imaging. Methods The charts of patients who underwent parathyroidectomy at three tertiary centers between the years 2012 and 2021 were retrospectively reviewed. Patients were defined as MIP candidates with either concordant preoperative imaging or a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Over the years review of the data on use of IPM in the localized patients has indicated that routine use of IPM may not be necessary for successful parathyroidectomy [2][3][4]. A retrospective analysis published in this current edition by Eligal et al hypothesizes that in patients with a localized preoperative imaging study (single or concordant imaging), the need for IPM to demonstrate surgical cure is unnecessary as it is unlikely to alter intraoperative management [5]. They further aimed to seek characteristics of patients who would benefit from use of IPM in whom it is likely to influence intraoperative management.…”
mentioning
confidence: 99%
“…Over the years review of the data on use of IPM in the localized patients has indicated that routine use of IPM may not be necessary for successful parathyroidectomy [2][3][4]. A retrospective analysis published in this current edition by Eligal et al hypothesizes that in patients with a localized preoperative imaging study (single or concordant imaging), the need for IPM to demonstrate surgical cure is unnecessary as it is unlikely to alter intraoperative management [5]. They further aimed to seek characteristics of patients who would benefit from use of IPM in whom it is likely to influence intraoperative management.…”
mentioning
confidence: 99%